Size dependent conduction characteristics of catalyst-multi-walled carbon nanotube junction - Christopher Barnett (Carbon Letters, 2021)
Multi-walled carbon nanotubes (MWCNTs) grown by chemical vapor deposition retain the residual catalyst particles from which the growth occurred, which are considered a detriment to MWCNTs’ performance, especially electrical conductivity. The first direct measurements have been made of the electrical transport through the catalyst cap into the MWCNT using nanoscale 2-point-probe to determine the effects of the catalyst particle’s size and the diameter ratio with its associated MWCNT on the electrical transport through the catalyst cap as compared to the inherent conductivity of the MWCNT. The MWCNT diameter is independent of the catalyst size, but the ratio of the catalyst cap diameter to MWCNT diameter (DC/DNT) determines the conduction mechanism. Where DC/DNT is greater than 1 the resulting I–V curve is near ohmic, and the conduction through the catalyst (RC+NT) approaches that of the MWCNT (RNT); however, when the DC/DNT < 1 the I–V curves shift to rectifying and RC+NT >  > RNT. The experimental results are discussed in relation to current crowding at the interface between catalyst and nanotube due to an increased electric field.